INTELLIGENT HELMET DETECTION USING OPEN CV AND MACHINE LEARNING (International Journal of Food and Nutritional Sciences, 2022)
As we all know Helmet is essential for our daily lives. Our brain is a crucial organ where it controls our thoughts, memory and emotions. In 2020 there were nearly 159,000 deaths due to on account of motor cycle riders not wearing a helmet. Concerning total percentage of road accidents two-wheelers constituted the highest proportion of 44.5% and the age group of persons involved in those tragedies are in-between 15 to 49 years. In this regard we want to curtail this risk and we have developed a project using Machine Learning and OPEN CV tools for Helmet Detection. We also use a camera module to detect the face of a person. The dataset is a set of images which is fed to the ML model and it processes it and outputs the real time status of the person/driver is wearing a helmet or not.By using YOLO algorithm, I created a predictive model that can be able to detect persons who are riding motorcycles without helmet in any condition.